Effects of copolymer microstructure on the properties of electrospun poly(l -lactide-co-ε-caprolactone) absorbable nerve guide tubes - Boontharika Thapsukhon (2018)
The main objective of this work has been to study the effects of copolymer microstructure, both chemical and physical, on the microporosity, in vitro hydrolytic degradability and biocompatibility of electrospun poly(l-lactide-co-ε-caprolactone), PLC, copolymer tubes for potential use as absorbable nerve guides. PLC copolymers with L: C compositions of 50: 50 and 67: 33 mol % were synthesized via the ring-opening copolymerization of l-lactide (L) and ε-caprolactone (C) at 120°C for 72 h using stannous octoate (tin(II) 2-ethylhexanoate) and n-hexanol as the initiating system. Electrospinning was carried out from solution in a dichloromethane/ dimethylformamide (7: 3 v/v) mixed solvent at room temperature. The in vitro hydrolytic degradation of the electrospun PLC tubes was studied in phosphate buffer saline over a period of 36 weeks. The microporous tubes were found to be gradually degradable by a simple hydrolysis mechanism leading to random chain scission. At the end of the degradation period, the % weight retentions of the PLC 50: 50 and 67: 33 tubes were 15.6% and 70.2%, respectively. Pore stability during storage as well as cell attachment and proliferation of mouse fibroblast cells (L929) showed the greater potential of the PLC 67: 33 tubes for use as temporary scaffolds in reconstructive nerve surgery. Copyright © 2013 Wiley Periodicals, Inc.